2019
DOI: 10.1158/1541-7786.mcr-18-0354
|View full text |Cite
|
Sign up to set email alerts
|

Combinations of Tyrosine Kinase Inhibitor and ERAD Inhibitor Promote Oxidative Stress–Induced Apoptosis through ATF4 and KLF9 in Medullary Thyroid Cancer

Abstract: Medullary thyroid carcinoma (MTC) originates from the C cells of the thyroid gland, which secrete calcitonin. Lymph node and distant metastases are frequently present at diagnosis. Activating mutations of RET, a driver oncogene in MTC that encodes a tyrosine kinase receptor, prevents apoptosis through inhibition of ATF4, a key transcriptional regulator of endoplasmic reticulum (ER) stress. We hypothesized that the combination of a tyrosine kinase inhibitor (TKI) and an ATF4 inducer promotes cell death by trigg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…For these reasons, terminal ERAD components inhibitors have been proposed as targets to specifically impair the survival of cancer cells [22, 91]. Blocking ERAD can also trigger cellular apoptosis [92].…”
Section: Methodsmentioning
confidence: 99%
“…For these reasons, terminal ERAD components inhibitors have been proposed as targets to specifically impair the survival of cancer cells [22, 91]. Blocking ERAD can also trigger cellular apoptosis [92].…”
Section: Methodsmentioning
confidence: 99%
“…Although various modes of action are still debated, it is broadly accepted that GCs mediate their anti-inflammatory and immunosuppressive effects by affecting macrophage viability and antitumor functionality (4). Several studies have demonstrated that tumor-derived KLF9 may act as a tumor suppressor by promoting apoptosis (8,19,20). Decreased KLF9 suppresses oxidative stress and apoptosis, subsequently promoting cancer progression (7).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, ATF4 increases the production of ROS, which can also be proapoptotic. The importance of ATF4 was demonstrated by blocking its transcription, which promoted apoptosis [43,44]. In contrast, translation of CHOP stimulates the transcription of protein phosphatase 1 regulatory subunit 15 (PPP1R15A/GADD34), TNF-related apoptosis-inducing ligand (TRAIL2), tribbles homolog 3 (TRB3), and, as a consequence, endoplasmic reticulum disulphide oxidase 1α (Ero1α).…”
Section: Participation Of Phospholipid Metabolism Products In Apoptosismentioning
confidence: 99%